Green is Graceful: Some Practical Lesson from the History of Islamic Science and Technology - Setia, Adi (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This essay claims to be self-critical and introspective in exploring modern western science, technology and innovation in relation to the religion of Islam. The article proposes learning from the Islamic scientific tradition in dealing with the current technoscientific mode of doing things. The author hopes to present ideas that could be used to build contemporary green and graceful science and technology. The article laments the deliberate, systemic destruction of nature and culture as the price for the technoscientific progress and recommends that humanity should begin listening to the wisdom of the ages in coping with the present day civilizational challenges.